Peculiarities of the Use of Information and Communication Technologies in the Development of Speech of Primary School Students - Mustafokulova Lobar Zayniddinovna (Procedia of Social Sciences and Humanities, 2022)
At a time when information technology is developing and has a negative impact on the spirituality of man, especially the younger generation, there is a need to develop the spirituality of young people, enrich their speech, influence their minds through ICT and further develop human feelings. In this sense, in the development of a healthy child, it is the tool they are interested in, that is, the development and implementation of methods of using information technology, which shows the relevance of the topic.